2020
DOI: 10.1021/acs.joc.0c01918
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Selenylindoles through Organoselenium-Promoted Selenocyclization of 2-Vinylaniline

Abstract: A novel metal-free one-pot protocol for the synthesis of potential biologically active molecules 3-selenylindoles via intramolecular cyclization/selenylation with simple 2-vinylaniline has been developed with moderate to good yield, thus representing it as a facile route to diverse substitution patterns around the indole core. The reaction proceeded smoothly with a broad substrate scope and excellent functional group tolerance. Moreover, the present synthetic route could be readily scaled up to gram quantity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Shao, Li and Chen realized an organoselenium-promoted synthesis of 3-selenylindoles 189 involving 2-styrylanilines 187 and diphenyldiselenide 188 with the aid of N -fluorobenzenesulfonamide (NFSI). 116 Substrates possessing ortho -, meta -, or para -substituents in the aromatic ring smoothly delivered the corresponding selenylindoles in good yields (up to 94%). Diselenides bearing electron-withdrawing (F, NO 2 ) and electron-donating groups (Me, OMe, naphthyl) in the aromatic ring were well tolerated.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…Shao, Li and Chen realized an organoselenium-promoted synthesis of 3-selenylindoles 189 involving 2-styrylanilines 187 and diphenyldiselenide 188 with the aid of N -fluorobenzenesulfonamide (NFSI). 116 Substrates possessing ortho -, meta -, or para -substituents in the aromatic ring smoothly delivered the corresponding selenylindoles in good yields (up to 94%). Diselenides bearing electron-withdrawing (F, NO 2 ) and electron-donating groups (Me, OMe, naphthyl) in the aromatic ring were well tolerated.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…In 2020, Zhao et al reported the organocatalytic ( N -fluorobenzenesulfonimide) one-pot synthesis of 3-selenylindoles through intramolecular cyclization/selenylation of 2-vinylaniline in moderate to good yield (up to 88%). The reaction was smoothly furnished, employing wide substrates and good functional group transformations, and could also be tolerated to gram scale ( Scheme 21 ) [ 71 ].…”
Section: The One-pot Multicomponent Combinatorial Synthesis Of Ose Co...mentioning
confidence: 99%
“…To illustrate the applicability of the amino-stilbenequinone hybrids as intermediates in the synthesis of heterocyclic compounds, 3a was submitted to the selenocyclization procedure recently described by Zhao et al 21 (Scheme 4). Selenylindole derivative 6a was isolated in 51% yield.…”
Section: Paper Synthesismentioning
confidence: 99%
“…Following the procedure described by Zhang et al, 21 a mixture of diphenyldiselenide (0.4 mmol, 125 mg), N-fluorobenzenesulfonimide (NFSI; 0.8 mmol, 252 mg), and 3a (0.4 mmol, 110 mg) in pyridine (4 mL) was heated at 110 °C in a pressure tube for 4 h. After cooling to r.t., the mixture was treated with sat. aq NaHCO 3 (20 mL) and extracted with EtOAc (3 × 15 mL).…”
Section: Selenocyclization Of Amino-stilbene-quinone 6amentioning
confidence: 99%